PPE decontamination to overcome PPE shortage in rural area during pandemic - Abdurrahman Kharbat; Habib Abla; Mahmud Alkul; Ranger Kile; Justin White; Cynthia Reinoso Webb; Steven M. Presley; Min H. Kang (Elsevier, 2021)
Summary: Despite remarkable developments in healthcare, the world was not ready to stop the spread of the novel COVID-19 pandemic almost a century after the great influenza pandemic. The explosive increase in the number of patients stalled the healthcare system, and the first and apparent issue was the shortage of personal protective equipment (PPE). Our group established a system using a hydrogen peroxide vaporization method to decontaminate and reuse N95 respirators for healthcare workers. The system decontaminated over 12,000 units of PPE to cover institutions in West Texas. This service provided support at the most needed time during the pandemic.